Glycemic Control Determinant of Diabetes Mellitus Patients - I Wayan Sukawana; I Made Sukarja; Listina Ade Widya Ningtyas; Ni Luh Putu Yunianti Suntari Cakera; Ni Made Juniari (KHD-Production, 2023)
Diabetes Mellitus (DM) is a chronic disease that cannot be cured. Complications in DM are the main cause of blindness, kidney failure, heart attacks, strokes, and amputations of the lower limbs. Various problems in DM can be prevented by controlling DM. DM control is influenced by individual factors and external factors. This study aims to determine the determinants of DM control on DM control parameters. The study was carried out with a cross-sectional design on 31 DM patients who were taken consecutively in July 2022 at the Ubud I Gianyar Health Center. The data collected in this study were HbA1c levels, blood glucose levels (fasting and 2 hours post-prandial), systolic and diastolic blood pressure. The results obtained are factors of age, gender, duration of DM, and dietary adherence together had a significant effect of 75.6% (p-value = 0.00) on HbA1c control. There is a significant contribution of 39.5% to systolic control. Has a significant effect (p-value omnibus test = 0.013) of 45.2% on controlling fasting glucose levels. The conclusion is that DM control by intervening modifiable factors such as emphasizing the importance of dietary adherence.